Towards an Inclusive Economy - Megan Claridge; Ron Crawford; Hauraki Greenland; Roger Hurnard; Benedickte Jensen; Geoff Lewis; Nick Mays; Murray Petrie; Roger Procter (New Zealand Government, The Treasury, 2001)
There has recently been a rapid growth in international literature and research on the links between economic growth and social capability and their impact upon well-being. This paper draws on that literature to build upon previous Treasury work at the intersection of economic and social policy. It examines the relationship between a productive economy and a society that enjoys high levels of participation, connection and cohesion, and their combined impact of peoples' well-being. It suggests that the objective in an inclusive economy is to improve the well-being of New Zealanders by directing policy to ensure that there are broad based opportunities to participate in society and the economy. The paper notes the 'virtuous' and 'vicious' circles that can occur when positive or negative interrelationships arise as a result of the above links. It suggests that there are five broad policy themes that are particularly important for building a more inclusive New Zealand economy. In particular there are a small number of policy areas where there appear to be opportunities for gains in equity and participation while being neutral or even positive for growth. These opportunities lie in focusing on education and jobs in the lower part of the distribution of attainment and skills; on strengthening Maori institutions and governance; and improving understanding of and reporting of the results of government action. Three Treasury companion papers to this one expand on particular aspects of the inclusive economy. They are Reducing Disparities in an Inclusive Economy (forthcoming), Human Capital and the Inclusive Economy and Geography and the Inclusive Economy: A Regional Perspective.
Keywords: A1; H0; O2; R1; 330; social capital; human capital; well being; economic growth; economic geography; values; governance